Overcoming the Paradox of Productivity and Self-awareness: The Key to Finding Family Harmony - Prasetyo, Eko Agus; Erfany, Muhammad Nurullah; Sholichatun, Yulia; Mangestuti, Retno; Rahayu, Iin Tri (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2025)
Abstract: Amid demands for high productivity in the digital economy, many workers experience a decline in the quality of family relationships and personal well-being. This study raises the phenomenon of the productivity paradox, which is a condition in which increased work efficiency triggers household stress and conflict. The purpose of this study is to analyze the influence of the productivity paradox and self-awareness on family harmony in industrial and startup sector workers in the Java region. A quantitative method was used involving 200 respondents, and the analysis was conducted using multiple linear regression. The results showed that both (1) the productivity paradox (B = 0.285; p 0.001) and self-awareness (B = 0.578; p 0.001) had a significant effect on family harmony, with the contribution of self-awareness being more dominant. (2) The Adjusted R² value of 0.677 indicates that both variables explain 67.7% of the variation in family harmony. (3) These results confirm that healthy productivity management and strengthening self-awareness are key to creating a harmonious family amidst complex work pressures. This study provides practical and theoretical contributions in the development of work-family balance policies and self-awareness-based psychological interventions.Keywords: Productivity Paradox; Self-awareness; Family Harmony; Work Stress; Life Balance